Automatic multilevel image segmentation based on fuzzy reasoning - Tang, Liang (Image analysis and stereology, 2004)
An automatic multilevel image segmentation method based on sup-star fuzzy reasoning (SSFR) is presented. Using the well-known sup-star fuzzy reasoning technique, the proposed algorithm combines the global statistical information implied in the histogram with the local information represented by the fuzzy sets of gray-levels, and aggregates all the gray-levels into several classes characterized by the local maximum values of the histogram. The presented method has the merits of determining the number of the segmentation classes automatically, and avoiding to calculating thresholds of segmentation. Emulating and real image segmentation experiments demonstrate that the SSFR iseffective.
Keywords: Image Processing, Computer-Assisted; Mehka logika; Slika, obdelava z računalnikom; Fuzzy Logic; stereologija; obdelava slik